Modern weapons and military equipment for issue 2-2022 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2022)
Russian army receives first modernized 203mm 2S7M Malka self-propelled howitzers,Can NATO’s Javelin Missile Wipeout Russia’s Tanks?Russia’s Predator-Like Drone Is Now Shooting Down Other Drones,Radar developers adapt for tracking hypersonic threats.
Keywords: military equipment; weapons